Infrastructure and Technology Management Contributions from the Energy, Healthcare and Transportation Sectors (Innovation, Technology, and Knowledge Management,, 2018)
This book presents emerging technology management approaches and applied cases from leading infrastructure sectors such as energy, healthcare, transportation and education. Featuring timely topics such as fracking technology, electric cars, Google's eco-friendly mobile technology and Amazon Prime Air, the volume's contributions explore the current management challenges that have resulted from the development of new technologies, and present tools, applications and frameworks that can be utilized to overcome these challenges. Emerging technologies make us rethink how our infrastructure will look in the future. Solar and wind generation, for example, have already changed the dynamics of the power sector. While they have helped to reduce the use of fossil fuels, they have created management complications due to their intermittent natures. Meanwhile, information technologies have changed how we manage healthcare, making it safer and more accessible, but not without implications for cost and administration. Autonomous cars are around the corner. On-line education is no longer a myth but still a largely unfulfilled opportunity. Digitization of car ownership is achievable thanks to emerging business models leveraging new communication technologies. The major challenge is how to evaluate the relative costs and benefits of these technologies. This book offers insights from both researchers and industry practitioners to address this challenge and anticipate the impact of new technologies on infrastructure now and in the future.